Protective Effects of Nootkatone on Renal Inflammation, Apoptosis, and Fibrosis in a Unilateral Ureteral Obstructive Mouse Model - Chang-Mu Chen (MDPI AG, 2021)
Nootkatone is one of the major active ingredients of Alpiniae oxyphyllae, which has been used as both food and medicinal plants for the treatment of diarrhea, ulceration, and enuresis. In this study, we aimed to investigate whether nootkatone treatment ameliorated the progression of chronic kidney diseases (CKD) and clarified its underlying mechanisms in an obstructive nephropathy (unilateral ureteral obstructive; UUO) mouse model. Our results revealed that nootkatone treatment preventively decreased the pathological changes and significantly mitigated the collagen deposition as well as the protein expression of fibrotic markers. Nootkatone could also alleviate oxidative stress-induced injury, inflammatory cell infiltration, and renal cell apoptotic death in the kidneys of UUO mice. These results demonstrated for the first time that nootkatone protected against the progression of CKD in a UUO mouse model. It may serve as a potential therapeutic candidate for CKD intervention.